Comparative Study on the Mythological Archetypes of the Forest in The Scarlet Letter and The Wilderness (International Journal of Language, Literacy and Translation, 2025)
Myths reflect the wisdom of ancient people. In the mid-20th century, Northrop Frye proposed archetypal criticism (myth criticism) and claimed that literature is displaced mythology; in other words, literary works are imitations of myths. The forest plays a significant role in mythology and is an essential imagery for archetypal criticism. As the primitive home of humankind, the forest is more than a vegetation world in literature; it is endowed with profound cultural implications, providing the motifs for literature. The forest imagery in The Scarlet Letter by Nathaniel Hawthorne, a well-known American Romantic novelist, and The Wilderness (Yüan-yeh) by Cao Yu (Ts’ao Yü), a prominent Chinese playwright, displaces mythological archetypes. However, due to the diverse cultures of the authors and the different themes they intended to convey, the mythological archetypes of the forest in the two works have similarities and differences. According to the holy scriptures and tales from Greek mythology, by using myth and archetypal criticism and qualitative research methods such as comparative method, biographical approach, and textual analysis, this paper attempts to analyze the similarities and differences between the mythological archetypes of the forest in The Scarlet Letter and The Wilderness to reveal the resemblance and diversity of human culture, psychology, and literary creation, as well as the significance of myth to literature. Findings show that the forest imagery in both works primarily displaces the archetypes of the Bible and Greek mythology and that the displacement focuses on the themes of atonement and redemption, expressing both authors’ ideals of goodness and self-redemption.